2012
DOI: 10.1007/s00737-012-0292-0
|View full text |Cite
|
Sign up to set email alerts
|

Parental care and control during childhood: associations with maternal perinatal mood disturbance and parenting stress

Abstract: This study examined the associations between perceived parental care and control in childhood and maternal anxiety, depression and parenting stress during the transition to parenthood. Eighty-eight women completed the Parental Bonding Instrument, self-report measures of anxiety and depression and a structured diagnostic interview (Mini-plus International Neuropsychiatric Interview) during the third trimester of pregnancy. The MINI-Plus and anxiety and depression measures were re-administered at 7 months postpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 47 publications
7
23
0
3
Order By: Relevance
“…These data were consistent with findings that indicated that prenatal attachment improved the ability of mothers to be sensitive to their own children's needs and protect them . Moreover, they constituted a significant confirmation of the attachment intergenerational transmission theory advanced by Bowlby, which showed how the mothers’ attachment pattern to their parents, in particular to their mothers, plays an important role in their future parenting .…”
Section: Discussionsupporting
confidence: 88%
“…These data were consistent with findings that indicated that prenatal attachment improved the ability of mothers to be sensitive to their own children's needs and protect them . Moreover, they constituted a significant confirmation of the attachment intergenerational transmission theory advanced by Bowlby, which showed how the mothers’ attachment pattern to their parents, in particular to their mothers, plays an important role in their future parenting .…”
Section: Discussionsupporting
confidence: 88%
“…Failure of the new parent to identify an adequate internal blueprint for caregiving, such as might occur in individuals who did not receive appropriate caregiving in their own childhoods, could be associated with role confusion and risk for depression 13 . The findings that adult attachment style [14][15][16] and parenting style experienced in childhood 17 strongly predict perinatal depression are consistent with this second potential causal pathway.…”
Section: Allostatic Load Versus Role Transition In Risk For Perinatalsupporting
confidence: 63%
“…By using these care and protection scores, they defined four parenting styles, namely, optimal parenting (high care/low protection), affectionate constraint (high care/high protection), neglectful parenting (low care/low protection), and affectionless control (low care/high protection). Subsequent studies36 show that depressed patients are prone to perceive that they were exposed to affectionless control parenting.…”
Section: Introductionmentioning
confidence: 99%